Sociodemographic Risk Factors Of Dementia Among Elderly Of Bumiputeras In Sarawak - Zurraini, Binti Arabi; Nazifah, H.; Syed Alwi, Bin Syed Abdul Rahman; Helmi, H. (2015)
The population in Malaysia is ageing similar to other parts of the world. Thus, the prevalence of dementia will gradually increase. Bumiputera population consists of 74.8% of the total population in Sarawak, the largest state in the whole of Malaysia. However, data regarding mental health among this group of population is limited.